Gestão competitiva em empresas brasileiras: a prática da estratégia por meio de suas visões, ferramentas e atores do processo - Maia, Jonas Lucio (2010)
The complexity assigned to the strategy term has been largely discussed in the literature. The large amount of theoretical contributions to this issue, brought by several knowledge areas; the different tools proposed by academicians and consultants to operationalize its concepts, the plurality of actors that play their roles inside the organizational field are just some examples of the building blocks of such complexity. Also relevant to this discussion is the movement named Strategy as Practice , initiated by European researchers in order to bring a sociological focus to organizational strategies, considering them as something a company does instead of something a company has. Thus, the main goal of this thesis is to identify and compare how Brazilian companies actually practice their competitive strategy, and to what extent/in which way such practice is aligned with the main firm s idiosyncratic variables and with their competitive environments. In order to achieve such goal, this work took advantage of a mixed research method, with a survey with companies listed on Brazilian Stock Exchange and six case studies. Concerning industry perception and company praxis, the main findings indicate that: (1) the internal and external views of competitive advantage are, indeed, perceived as complementary regarding firm strategies; (2) even in more traditional industries, companies perceive their environment as dynamic, due to companies´ mobility, group consolidations or internal rivalry; (3) even in industry with high barriers to entry, firms regularly adopt a surveillance approach to monitor newcomers; (4) innovation tends to be more focused on process than on products, and there is a gap between intended and implemented innovation; (5) the perception of resources and competences spread throughout company networks suggests that controlling these resources may be more important than owning them; (6) at least in the studied companies, low relevance has been assigned to knowledge as a strategic advantage. Regarding strategy practices: (7) an annual strategy planning cycle takes place, focused on formulation activities and perceived as static in nature; (8) workshops and performance meetings were the most often identified strategic events; (9) strategy tools were perceived as highly effective and mainly targeted at structuring analysis and ensuring strategy implementation, with special emphasis to the abundance of financial tools and lack of creativity ones. Concluding, concerning practitioners: (10) it could by empirically identified the existence of an organizational structure responsible for companies strategic planning, generally close to financial areas; (11) those generally involved in strategic activities show a primarily analytical profile, with low presence of women; (12) senior executives have developed their careers mainly inside the company or inside the industry, with relevant business knowledge, while middle management plays its role by implementing decisions made by high executives; (13) consultancies tend to be highly used, and their recontracting is contingent upon the patterns of their involvement in the strategy process; (14) business press has been assigned low relevance, being substituted in some cases by financial releases or by information from industry entities.